Ray tracing design-optimization & experimental validation of water based optical filter to reduce solar PV module heating - Satish Kumar Yadav; K.S. Vishnu Varma; Sidra Khatoon; Vishwadeep Chakraborty; Jyotsna Singh; Rajendra Bahadur Singh; S.M. Mozammil Hasnain; Rustem Zairov (Case Studies in Thermal Engineering)
The operating temperature of a photovoltaic (PV) module significantly impacts its efficiency. Increased temperatures reduce the efficiency due to a negative thermal coefficient, which decreases its power above standard test conditions (25 °C, 1000 W/m2). This research targets the reduction of thermal load on PV modules through the incorporation of a water-based optical filter, designed and optimized using ray tracing techniques. The optimal thickness for the glass was determined as 3 mm and 5 mm for the water layers of the filter, providing the best yield. The filter effectively absorbs 92 % of the infrared radiation and 47 % of the ultraviolet spectral flux, significantly reducing heat-induced efficiency losses in the PV module. Water-based optical filter system reduces the module temperature up to 9.80 °C. The optical filter-based PV system achieved a 4.56 % increase in electrical efficiency compared to the reference module, with an average efficiency of 12.19 %. The heated water, reaching up to 48.25 °C, can be reused for various industrial processes, providing both cooling for PV modules and a hot water source, making it versatile and efficient for regions needing both electricity and hot water.